Pengaruh Terapi Musik Langgam Jawa Terhadap Penurunan Skala Nyeri Dismenorea Di SMA Khadijah Surabaya: Penelitian Quasy Experimental - Irma Putri Rahardini, - (2013)
Dysmenorrhea is menstrual pain that present as cramp, ranging from mild to severe, which may disturb daily activities. Javanese traditional music therapy is a method to reduce the dysmenorrhea pain scale. The objective of this study was to analyze the effect of Javanese traditional music therapy on the reduction of dysmenorrhea pain scale. This research was using quasy experimental design. The population was female students who had dysmenorrhea in Khadijah Senior High School. Sample recruited using purposive sampling through matching process. Twenty respondents use in the research divided in two group. The first group were treatment group, they were receiving Javanese traditional music therapy with the tittle Gambang Suling, Lir Ilir and Yen Ing Tawang. The other group were control group, no treatment were given to control group. The demography data were collected using questionnaire. The pain scale data were collected using observation Bourbonais Scale. The result showed that Javanese traditional music therapy effect reduce dysmenorrhea pain scale, in treatment group had significant value by using Wilcoxon Signed Rank Test are p = 0,004 for Javanese traditional music therapy. Mann Whitney U test, the result showed p = 0,010 mean there was a difference between control group and treatment group. It can be concluded that Javanese traditional music therapy can reduce the dysmenorrhea pain scale. Further studies about combined other methods to reduce dysmenorrhea pain using larger sample were needed or other music.